2017
DOI: 10.7324/japs.2017.71224
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Characterization of Sulfamethoxazole-Trimethoprim Cocrystal by Milling Process

Abstract: The purpose of this study was to describe and characterize co-crystal formation of sulfamethoxazole and trimethoprim. The co-crystal formation was carried out by solid state milling process. Co-crystal by solution cocrystallization and physical mixture were also prepared as a comparison. The potential co-crystalline phase was characterized by powder X-ray Diffraction (PXRD), thermal analysis differential scanning calorimetry (DSC), scanning electron microscope (SEM), and Fourier transform Infrared (FT-IR) spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…A multi-component crystal phase is formed if the PXRD pattern of the binary mixture is distinct from its starting components (Karagianni et al, 2018;Thakral et al, 2018). The PXRD pattern of the present study (Figure 2) showed specific diffraction peaks of TMP, which are similar to a previous report (Zaini et al, 2017). The unique pattern of TMP-MA, which established new peaks, supports the formation of a distinct crystalline phase composed of both TMP and MA.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A multi-component crystal phase is formed if the PXRD pattern of the binary mixture is distinct from its starting components (Karagianni et al, 2018;Thakral et al, 2018). The PXRD pattern of the present study (Figure 2) showed specific diffraction peaks of TMP, which are similar to a previous report (Zaini et al, 2017). The unique pattern of TMP-MA, which established new peaks, supports the formation of a distinct crystalline phase composed of both TMP and MA.…”
Section: Discussionsupporting
confidence: 89%
“…The molecules in the crystal lattice are bonded by non-covalent intermolecular interactions, such as hydrogen bonding Incorporating active pharmaceutical ingredients into multi-component crystals has been shown to enhance their physicochemical properties, including solubility and dissolution rate (Dwichandra Putra et al, 2018;Yuliandra et al, 2019), compressibility (Rahman et al, 2012;Paramanandana et al, 2020), physical and chemical stability (Vangala et al, 2011;Sopyan et al, 2017), bioavailability, and pharmacological effectiveness (Shete et al, 2015;Yuliandra et al, 2018). Multi-component crystals of TMP have been extensively investigated, including a cocrystal with sulfamethoxazole and salts of trimethoprim with cinnamic acid, acetic acid, formic acid, maleic acid, and mefenamic acid (Bryan et al, 1987;Prabakaran et al, 2001;Umadevi et al, 2002;Muthiah et al, 2006;Zaini et al, 2017;Bhattacharya et al, 2020). However, to the best of our knowledge, there are no reports on the formation of multi-component crystals of TMP with malic acid (MA) nor an investigation into its physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The technique was used to assess fusion temperature and enthalpy values. The crimped drug was heated to 400 °C at the heating rate of 10 °C/min as per the method adopted before . After completion of the maximum temperature, the system was cooled by purging with nitrogen gas (60 mL/min). , …”
Section: Methodsmentioning
confidence: 99%
“…, the C=N group from 1636.70 cm −1 to 1589.37 cm −1 and the C=H group from 1464.00 to 1452.42 cm −1 . dissolution rate and solubility of trimethoprim through multicomponent crystalline phase with several excipients [12], [13], [14], [15], [16], [17], [24]. S ome factors may contribute to the increment of solubility and dissolution rate of multicomponent crystals of trimethoprim and citric acid.…”
Section: Figure 2a Displays a Thermogram Of Trimethoprim Which Shows ...mentioning
confidence: 99%
“…Several multi-component crystal phases of trimethoprim include cocrystals, some of which have been reported including salts with sulfamethoxazole, mefenamic acid, cinnamic acid, formic acid, acetic acid, malic acid, and maleic acid [8], [12], [13], [14], [15], [16], [17]. However, so far there has been no report of multicomponent crystal phases of trimethoprim with citric acid.…”
Section: Introductionmentioning
confidence: 99%